PENGEMBANGAN MODEL TEAMS GAMES TOURNAMENTS PADA PEMBELAJARAN BAHASA ARAB: ANALISIS DAMPAK PADA MAHĀRAH AL-KALĀM MAHASISWA - Asep Sunarko (SPESIFIK: Jurnal Pendidikan dan Pembelajaran, 2025)
The purpose of this study was to create a Teams Games Tournaments (TGT) model based on the Dick, Carey, and Carey design for Arabic language learning and to examine how TGT affects students' speaking skills (mahārah al-kalām). This study was conducted using a mixed-method approach, meaning that quantitative data consisted of pretest and posttest scores, and qualitative data consisted of interviews and classroom observations. The results showed that the implementation of the TGT model improved students' speaking interactions, fluency, accuracy, and motivation. Students became more active in competitive activities, more confident in speaking, and better at constructing sentences. This model also encouraged systematic, enjoyable, and interactive learning, and encouraged peer-assisted learning and communication skills. This study provides practical contributions for lecturers in creating innovative Arabic language learning methods that focus on oral communication skills.